Preparation method and application of PAT / FS-50 heterogeneous composite membrane material
By modifying the micro-nanostructure coating of hydrophilic groups on the surface of the membrane and introducing the fluorine surfactant FS-50, a heterogeneous superoleophobic/hydrophilic membrane surface is constructed, which solves the problem that traditional membrane materials are easily blocked in oil-water separation, and achieves high-efficiency and stable oil-water separation performance and long-life membrane materials.
Patent Information
- Application Number
- CN202210847554.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-07-19
AI Technical Summary
The existing membrane materials are easily blocked by oil droplets during the oil-water separation process, resulting in a reduced separation efficiency. The durability and circulation performance of traditional membrane materials are insufficient, making it difficult to achieve long-term stable use.
The coating of micro-nanostructures of hydrophilic groups on the membrane surface is modified, and the fluorine surfactant FS-50 is introduced to construct a heterogeneous superoleophobic/hydrophilic membrane surface, reducing the membrane surface energy, improving separation flux and anti-fouling properties.
It significantly improves the separation efficiency of oil-water separation, optimizes the circulation and chemical stability of the membrane, extends the service life of the membrane material, and maintains excellent self-cleaning performance.
Smart Images

Figure CN115155333B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a PAT / FS-50 heterogeneous composite membrane material, belonging to the technical field of environmental functional material preparation. Background Art
[0002] With the development of industry, oily wastewater from petrochemical, food, textile, metal and machinery industries has caused urgent pollution problems in many fields such as energy recovery and marine protection. Oily wastewater not only damages the ecological environment, but also endangers human health. Its treatment has always been a global problem, especially the treatment of high-viscosity and high-concentration emulsified oil. At present, the separation methods of oily wastewater include gravity method, biological method, combustion method, electrochemical method and centrifugal method. However, these methods cannot achieve the ideal separation effect for the treatment of emulsified oil. Membrane separation method is widely used in sewage treatment due to its excellent performance such as low energy consumption, no secondary pollution, simple operation and strong adaptability. However, the interface wetting characteristics of traditional membrane materials are not significant, and the membrane surface is easily attached by oil droplets. In practical applications, it often leads to a sharp drop in flux, a significant reduction in separation efficiency, and a short service life of the membrane, thereby increasing production costs. In order to solve these problems, in the past decade, new membrane materials with super wettability have received extensive attention and research in sewage treatment, especially for the separation of oil-water mixtures and emulsified oil. At present, the superwetting membrane materials used in oil-water separation are mainly divided into two types: superhydrophobic / superoleophilic membrane materials and superhydrophilic / underwater superoleophobic membrane materials. With the continuous deepening of research, researchers have found that superhydrophobic / superoleophilic membrane materials have some difficult-to-overcome defects, that is, during the oil-water separation operation, the pores on the surface of superhydrophobic / superoleophilic membrane materials are easily blocked by oil droplets with high viscosity, which greatly reduces the separation efficiency and seriously damages the recycling performance and reusability of membrane materials, making it impossible for oil-water separation to proceed normally. Superhydrophilic / underwater superoleophobic membrane materials have the advantages of high efficiency, low energy consumption, not easy to cause secondary pollution, and long life. Therefore, superhydrophilic / underwater superoleophobic membrane materials are considered to be the best superwetting materials for treating oil-water mixtures and water-in-oil emulsions.
[0003] For the superhydrophilic modification of membrane materials, rough micro-nano structures and hydrophilic groups are indispensable. Based on this principle, researchers have developed a variety of modification strategies to prepare superhydrophilic surfaces. Commonly used superhydrophilic modification methods include nanoparticle modification, hydrogel surface grafting zwitterionic polymer method, hydrophilic polymer coating method, mineral deposition adhesion method, electrostatic spraying method, etc. These methods all introduce a large number of hydrophilic groups and rough micro-nano structures on the surface of the base membrane to construct a superhydrophilic / underwater superoleophobic surface. Although major breakthroughs have been made in the research of superhydrophilic and underwater superhydrophobic membrane materials, the problem of membrane surface contamination by oil droplets has always plagued researchers.
[0004] Inspired by the self-cleaning effects of lotus leaves and springtails, researchers have developed low-surface-energy materials based on the "pollution repellent" mechanism, which weakens the adhesion to pollutants and quickly removes pollutants under the action of fluid shear force. They are widely used in marine antifouling, anti-pollution membranes and other fields. Recently, Professor Jiang Zhongyi's research group used fluorinated amphiphilic modifiers to prepare chemically heterogeneous hydrogel ultrafiltration membranes, constructing a synergistic antifouling mechanism of "pollution resistance" and "pollution repellent", and promoting the development of antifouling self-cleaning membranes. Since the surface energy of oil is lower than that of water, for chemically homogeneous surfaces, if they are superhydrophilic in the air, they will inevitably be superoleophilic. Fluorocarbon surfactants are composed of a high-surface-energy hydrophilic head group and a low-surface-energy amphiphilic fluorocarbon chain, which can effectively reduce the surface energy of the membrane and improve the self-cleaning and recycling performance of the membrane. Currently, the most commonly used method reported in the literature is the use of perfluorooctanoate (PFO) in combination with polyelectrolytes and TiO 2 Nanoparticles, chitosan, etc. are assembled, but the water resistance and salt resistance of the system are poor. Anions in seawater (such as chloride ions and sulfate ions) will exchange ions with PFO, destroying its chemical structure, causing the membrane material to have a series of problems during use, such as short life, poor cyclability, and reduced separation efficiency. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention proposes a simple strategy. First, a coating with a micro-nano structure having a hydrophilic group is modified on the membrane surface. The coating is obtained by the Michael addition reaction or Schiff base reaction of polyphenol with 3-aminopropyltriethoxysilane (APTES) and tetraethyl orthosilicate (TEOS) and amino groups, referred to as PAT coating. Then, a fluorinated surfactant (FS-50) with good stability is introduced to reduce the membrane surface energy and establish a heterogeneous superoleophobic / hydrophilic membrane surface, thereby improving the separation flux while optimizing the membrane's circulation performance, chemical stability and self-cleaning performance, and extending the service life of the membrane material. .
[0006] The technical solution adopted by the present invention is:
[0007] A method for preparing a PAT / FS-50 heterogeneous composite membrane material is carried out according to the following steps:
[0008] (1) placing the porous membrane in anhydrous ethanol and ultrasonicating it to clean the membrane surface and remove the bubbles in the membrane pores, then taking out the porous membrane and wiping off the excess liquid on the membrane surface with filter paper;
[0009] (2) preparing a polyphenol aqueous solution of a certain concentration;
[0010] Prepare a mixed solution A of 3-aminopropyltriethoxysilane (APTES) and tetraethyl orthosilicate (TEOS) ethanol solution;
[0011] The polyphenol aqueous solution is mixed with the mixed solution A to obtain a mixed solution B;
[0012] (3) The porous membrane is immersed in the mixed solution B prepared in step (2), and after a period of reaction, it is taken out and repeatedly washed with distilled water for several times, and the excess liquid on the surface of the membrane is wiped off with filter paper, and then immersed in a certain concentration of fluorosurfactant FS-50 solution, and after a period of reaction, it is washed several times with distilled water again, and then placed in an oven for drying to obtain a PAT / FS-50 heterogeneous composite membrane material.
[0013] In step (1), the porous membrane is a hydrophilic PVDF, a hydrophobic PTFE or a hydrophobic PES membrane material.
[0014] In step (2), the polyphenol is tannic acid (TA), anthocyanin (OPC) or gallic acid (GC),
[0015] The polyphenol aqueous solution has a concentration of 1-5 mg / mL;
[0016] In the mixed solution A, the concentration of APTES is 1-5 mg / mL, the concentration of TEOS is 1-5 μL / mL, and the volume ratio of the polyphenol aqueous solution to the mixed solution A is 1:1;
[0017] In step (3), the porous membrane is immersed in the mixed solution B for 8-12 hours;
[0018] In step (3), the mass percentage concentration of the FS-50 solution is 1-4%, the immersion time in the FS-50 solution is 20-60 minutes, and the rinsing time with distilled water is 3.0 to 5.0 seconds.
[0019] In step (3), the drying temperature is 55-60° C. and the drying time is 2-4 min.
[0020] The PAT / FS-50 heterogeneous composite membrane material of the present invention is used in the field of oil-water separation.
[0021] The operating pressure of the oil-water separation test was 0.01-0.05 MPa, and the water-in-oil emulsion used was a n-hexane-water emulsion with a volume ratio of 1:99.
[0022] Technical advantages of the present invention:
[0023] (1) The present invention uses a simple surface modification method to modify the surface of the porous membrane with a hydrophilic coating having a rough micro-nano structure, and then further introduces FS-50 to construct a heterogeneous chemical structure on the membrane surface, thereby improving the separation flux and anti-fouling performance of the composite membrane. The preparation method is simple to operate, low in cost, and has no pollution to the environment, which is in line with the concept of environmental friendliness.
[0024] (2) When using the PAT / FS-50 heterogeneous composite membrane to separate oil-water emulsions, it exhibits excellent separation performance and is suitable for a variety of oil-water emulsions, with a separation efficiency of more than 99%.
[0025] (3) The PAT / FS-50 heterogeneous composite membrane has high separation flux, good stability, recyclability, and self-cleaning performance. After repeatedly separating 100 mL of water-in-oil emulsion with a volume ratio of 1:99 for 6 times, it still maintains excellent separation performance, indicating that it is of practical significance as an oil-water separation membrane material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 These are SEM images of the original PVDF membrane (a, b) and the PAT / FS-50-PVDF-1 (c, d) heterogeneous composite membrane in Example 1.
[0027] Figure 2 Schematic diagram of the underwater oil drop contact angle of Example 4.
[0028] Figure 3 These are the particle size diagrams of the oil-water emulsion of Example 5 before (a) and after (b) separation. DETAILED DESCRIPTION
[0029] In order to illustrate the technical solution and technical purpose of the present invention, the present invention is further introduced below in conjunction with the accompanying drawings and specific embodiments.
[0030] Embodiment 1:
[0031] Step 1: Cut the PVDF membrane into 2×2cm 2 The size of the square is placed in anhydrous ethanol for ultrasonic cleaning to achieve the purpose of cleaning the membrane surface and removing bubbles in the membrane pores. After taking it out, use filter paper to wipe off the excess liquid on the membrane surface. Prepare a 1mg / mL tannic acid (TA) aqueous solution, and a 1mg / mL and 1μl / mL 3-aminopropyltriethoxysilane (APTES) and tetraethyl orthosilicate (TEOS) ethanol mixed solution, mix the above two solutions, put them into the pretreated PVDF membrane, react for 12 hours, take it out, wash it repeatedly with distilled water 3-5 times, wipe off the excess liquid on the membrane surface with filter paper, and then immerse it in a 2% mass percentage FS-50 solution, react for 60 minutes, take it out, wash it again with distilled water 3-5 times, and then put it in an oven for drying. The PAT / FS-50-PVDF-1 heterogeneous composite membrane is obtained.
[0032] Figure 1 The SEM images of the original PVDF membrane (a, b) and the PAT / FS-50-PVDF-1 (c, d) heterogeneous composite membrane in Example 1 are shown in FIG. Figure 1It can be seen that the micro-nanoparticles are successfully loaded onto the surface of the PVDF membrane with a rough surface structure.
[0033] Step 2:
[0034] The prepared PAT / FS-50-PVDF-1 heterogeneous composite membrane was placed in an oil-water separation device. A small amount of distilled water was first used to wet the membrane surface. Then 100 mL of n-hexane-water emulsion with a volume ratio of 1:99 was poured into the oil-water separation device. The separation pressure was adjusted to 0.05 MPa for separation performance testing. In order to more accurately determine the oil-water separation performance of the composite membrane, each sample was tested 3 times. The entire experimental process was carried out under a pressure of 0.05 MPa, and the oil-water separation efficiency was calculated according to the following formula:
[0035] R(%)=(T 1 -T feed ) / (T 0 -T feed )
[0036] Where R is the separation efficiency, T feed is the average transmittance of the original emulsion (400-800nm), T 0 is the average transmittance of pure water (400-800nm), T 1 is the average transmittance (400-800 nm) corresponding to the filtrate after separation, and the above transmittances are all measured by ultraviolet spectrophotometer.
[0037] The experimental results show that the PAT / FS-50-PVDF-1 heterogeneous composite membrane has excellent oil-water separation performance, and its separation efficiency reaches 99.5%.
[0038] Embodiment 2:
[0039] Step 1: Cut the PVDF membrane into 2×2cm 2 The size of the square is placed in anhydrous ethanol for ultrasonic cleaning to achieve the purpose of cleaning the membrane surface and removing bubbles in the membrane pores. After taking it out, use filter paper to wipe off the excess liquid on the membrane surface. Prepare an aqueous solution of anthocyanin (OPC) with a concentration of 1 mg / mL, and an ethanol mixed solution of 3-aminopropyltriethoxysilane (APTES) and tetraethyl orthosilicate (TEOS) with concentrations of 2 mg / mL and 2μl / mL respectively. After mixing the above two solutions, put them into the pretreated PVDF membrane, take them out after reacting for 12 hours, wash them repeatedly with distilled water 3-5 times, wipe off the excess liquid on the membrane surface with filter paper, and then immerse them in a FS-50 solution with a mass percentage concentration of 2%, take them out after reacting for 60 minutes, wash them again with distilled water 3-5 times, and then put them in an oven for drying. The PAT / FS-50-PVDF-2 heterogeneous composite membrane is obtained.
[0040] Step 2:
[0041] The prepared PAT / FS-50-PVDF-2 heterogeneous composite membrane was placed in an oil-water separation device, and an oil-water separation experiment was performed according to the operation of step 2 in Example 1. The experimental results showed that the PAT / FS-50-PVDF-2 heterogeneous composite membrane had excellent oil-water separation performance, and its separation efficiency reached 99.9%.
[0042] Embodiment 3:
[0043] Step 1: Cut the PVDF membrane into 2×2cm 2 The square of size is placed in anhydrous ethanol for ultrasonic cleaning to achieve the purpose of cleaning the membrane surface and removing bubbles in the membrane pores. After taking it out, use filter paper to wipe off the excess liquid on the membrane surface. Prepare a gallic acid (GC) aqueous solution with a concentration of 1 mg / mL, and an ethanol mixed solution of 3-aminopropyltriethoxysilane (APTES) and tetraethyl orthosilicate (TEOS) with concentrations of 1 mg / mL and 1 μl / mL respectively. After mixing the above two solutions, put them into the pretreated PVDF membrane, take them out after reacting for 12 hours, wash them repeatedly with distilled water 3-5 times, wipe off the excess liquid on the membrane surface with filter paper, and then immerse them in a FS-50 solution with a mass percentage concentration of 3%, take them out after reacting for 60 minutes, wash them again with distilled water 3-5 times, and then put them in an oven for drying. The PAT / FS-50-PVDF-3 heterogeneous composite membrane is obtained.
[0044] Step 2:
[0045] The prepared PAT / FS-50-PVDF-3 heterogeneous composite membrane was placed in an oil-water separation device, and an oil-water separation experiment was performed according to the operation of step 2 in Example 1. The experimental results showed that the PAT / FS-50-PVDF-3 heterogeneous composite membrane had excellent oil-water separation performance, and its separation efficiency reached 99.9%.
[0046] Embodiment 4:
[0047] Step 1: Cut the PTFE film into 2×2cm 2The square of size is placed in anhydrous ethanol for ultrasonic cleaning to achieve the purpose of cleaning the membrane surface and removing bubbles in the membrane pores. After taking it out, use filter paper to wipe off the excess liquid on the membrane surface. Prepare a tannic acid (TA) aqueous solution with a concentration of 5 mg / mL, and an ethanol mixed solution of 3-aminopropyltriethoxysilane (APTES) and tetraethyl orthosilicate (TEOS) with concentrations of 5 mg / mL and 5 μl / mL respectively. After mixing the above two solutions, put them into the pretreated PTEE membrane, take them out after reacting for 12 hours, wash them repeatedly with distilled water for 3-5 times, wipe off the excess liquid on the membrane surface with filter paper, and then immerse them in a FS-50 solution with a mass percentage concentration of 4%, take them out after reacting for 60 minutes, wash them again with distilled water for 3-5 times, and then put them in an oven for drying. The PAT / FS-50-PTEE heterogeneous composite membrane is obtained.
[0048] Step 2:
[0049] The prepared PAT / FS-50-PTEE heterogeneous composite membrane was placed in an oil-water separation device, and an oil-water separation experiment was performed according to the operation of step 2 in Example 1. The experimental results showed that the PAT / FS-50-PTEE heterogeneous composite membrane had excellent oil-water separation performance, and its separation efficiency reached 99.9%.
[0050] Figure 2 Schematic diagram of underwater oil drop contact angle of Example 4. The contact angle of the heterogeneous composite membrane material is 158.5°, achieving underwater superoleophobicity, indicating that the PAT / FS-50-PTFE heterogeneous composite membrane has the potential for oil-water separation.
[0051] Embodiment 5:
[0052] Step 1: Cut the PES membrane into 2×2cm 2 The square of the size is placed in anhydrous ethanol for ultrasonic cleaning to achieve the purpose of cleaning the membrane surface and removing bubbles in the membrane pores. After taking it out, use filter paper to wipe off the excess liquid on the membrane surface. Prepare a tannic acid (TA) aqueous solution with a concentration of 1 mg / mL, and an ethanol mixed solution of 3-aminopropyltriethoxysilane (APTES) and tetraethyl orthosilicate (TEOS) with concentrations of 1 mg / mL and 1 μl / mL respectively. After mixing the above two solutions, put them into the pretreated PES membrane, take them out after reacting for 12 hours, wash them repeatedly with distilled water 3-5 times, wipe off the excess liquid on the membrane surface with filter paper, and then immerse them in a FS-50 solution with a mass percentage concentration of 4%, take them out after reacting for 1 hour, wash them again with distilled water 3-5 times, and then put them in an oven for drying. The PAT / FS-50-PES heterogeneous composite membrane is obtained.
[0053] Step 2:
[0054] The prepared PAT / FS-50-PES heterogeneous composite membrane was placed in an oil-water separation device, and an oil-water separation experiment was carried out according to the operation of step 2 in Example 1, except that the n-hexane-water emulsion was replaced with dichloroethane-water emulsion. The experimental results showed that the PAT / FS-50-PES heterogeneous composite membrane had excellent oil-water separation performance, and its separation efficiency reached 99.8%.
[0055] Figure 3 The particle size diagrams of the oil-water emulsion before (a) and after (b) separation in Example 5 show that there are almost no oil droplets in the filtrate after separation, indicating that the PAT / FS-50-PES composite membrane has practical application value.
Claims
1. A method for preparing a PAT / FS-50 heterogeneous composite membrane material, characterized in that: The composite membrane is based on a porous membrane, and the PAT micro-nano coating is loaded on the surface of the porous membrane; The steps include: (1) placing the porous membrane in anhydrous ethanol and ultrasonically cleaning the membrane surface and removing bubbles in the membrane pores, then taking out the porous membrane and wiping off excess liquid on the membrane surface with filter paper; (2) preparing a polyphenol aqueous solution; A mixed solution A of 3-aminopropyltriethoxysilane APTES and tetraethyl orthosilicate TEOS ethanol solution is prepared, and the polyphenol aqueous solution and the mixed solution A are mixed to obtain a mixed solution B; In mixed solution A, the concentration of APTES is 1-5 mg / mL, and the concentration of TEOS is 1-5 μL / mL; The concentration of the polyphenol aqueous solution is 1-5 mg / mL; The volume ratio of the polyphenol aqueous solution to the mixed solution A is 1:1; (3) immersing the porous membrane in the mixed solution B prepared in step (2), taking it out after the reaction, repeatedly washing it with distilled water several times, wiping off excess liquid on the membrane surface with filter paper, and then immersing it in a fluorosurfactant FS-50 solution, reacting for 20-60 minutes, washing it again with distilled water several times, and then putting it in an oven for drying to obtain a PAT / FS-50 heterogeneous composite membrane material; The mass percentage concentration of the FS-50 solution is 1-4%.
2. The preparation method according to claim 1, characterized in that In step (1), the porous membrane is a hydrophilic PVDF, a hydrophobic PTFE, or a hydrophobic PES membrane material.
3. The preparation method according to claim 1, characterized in that: In step (2), the polyphenol is tannic acid TA, anthocyanin OPC or gallic acid GC.
4. The preparation method according to claim 1, characterized in that: In step (3), the porous membrane is immersed in the mixed solution B for 8-12 hours.
5. The preparation method according to claim 1, characterized in that: In step (3), the drying temperature is 55-60° C. and the drying time is 2-4 min.
6. Use of the PAT / FS-50 heterogeneous composite membrane material prepared by the preparation method according to any one of claims 1 to 5 for oil-water separation.
Citation Information
Patent Citations
Hydrophobic polymer film composite coating hydrophiling modification method
CN106310958A
Non-selective oleophobic and hydrophilic material as well as preparation method and application thereof
CN109261127A